Influence of polymeric additives on the process of electro casting and structure of nanofibrous materials. - I. Yu. Filatov; N. A. Gruzdev; Yu. N. Filatov (Тонкие химические технологии, 2009)
The effect of addition of polymeric blends to spinning solution on fiber diameter and on structure of the electrospun nanofibrous materials is investigated.